Sleep disorders, Diagnosis, treatment and A Dentist’s role in early diagnosis and treatment of sleep disorders: A Review: sleep disorders and Dentists role - Devi, Devarathnamma MV; Bhat, Geeta; Hunakunti, Shreya; Bhat, Manohar; Sharma, Deepak; Rangappa, Janavathi (International Journal of Clinical and Biomedical Research, 2022)
Objective/Background: Sleep disorders are interdisciplinary and involve a number of specialties such as respiratory medicine, neurology, psychiatry, otolaryngology, and Dentistry. 87.5% of the patients with loud snoring suffer from sleep-disordered breathing, of which 72% complain of excessive daytime sleepiness. Controversial evidence exists on the association of sleep disorders as a primary or secondary risk factor for many common systemic conditions. Yet, sleep medicine is not given emphasis in medical school education. In addition, dentists now participate in the recognition and treatment of sleep disorders, Dentist’s role and involvement in the treatment and management of a sleep-disordered patient may be indirect or direct. Hence, this review explains sleep disorders, diagnosis and treatment, and the role of dentists in early diagnosis and treatment.